4 upland breeding lines with improved yield under low-input (P deficient) conditions in Madagascar - CGIAR Research Program on Rice (2020)
Upland breeding lines with improved yield under low-input (P deficient) conditions were identified through farmer-participatory selection on smallholder farms in Madagascar